A gender-responsive breeding approach to the intensification of sesame (Sesamum indicum L.) production in the Maradi region of Niger - Lawali, S.; Boureima, S.; Idi, S. (Frontiers Media, 2024)
Climatic variability and a decrease in soil fertility have had a detrimental effect on the productivity of the main rainfed crops in Niger (millet, sorghum, and cowpea) and led to a deterioration of the nutritional status and income of the country's farmers. The spatio-temporal variability in rainfall has led rural populations to diversify their farms by integrating sesame (Sesamum indicum L.) into their cropping systems because of its low water and fertilizer requirements. Sesame is increasingly becoming a significant source of income for farmers, and it contributes to their food and nutritional security. To boost the production of sesame and facilitate its rapid adoption, our breeding program focused on participatory breeding and varietal selection with the inclusion of gender-specific preferences, from the variety design to the evaluation of new lines on farms. This case study shows that, although women have more experience in sesame cultivation than men, they have less access to production factors such as land. This limited access is especially problematic, as recent trends in land tenure mean that the poorest are no longer able to exploit large areas of cultivable land. It also evidenced that the varietal preferences of sesame growers as well as the mastery of production techniques are a function of the livelihoods and the investment capacity of actors in the value chain. Our study found that men mainly prefer production traits, whereas women have fewer trait preferences, and their preferences tend to be related to marketing and processing. This finding highlights the contrasting roles and responsibilities between men and women in the sesame value chain. Therefore, the inclusion of complementary traits preferred by women and men, provided that they are not negatively correlated with a variety profile, will help meet the full range of needs across the value chain. We recommend the inclusion of gender research in setting breeding goals prior to variety design.